Differential cytokine expression profile in peripheral blood mononuclear cells of endometritic buffaloes - PATRA, MANAS KUMAR; KUMAR, HARENDRA; NANDI, SUKDEB (The Indian Journal of Animal Sciences, 2014)
The aim of present study was to elucidate the relative mRNA expression of certain cytokines, viz. interleukin- 1ß (IL-1ß), IL-8, tumor necrosis factor alpha (TNFa) and IL-4 in peripheral blood mononuclear cells (PBMCs) of endometritic buffaloes. Out of 15 buffaloes, 9 buffaloes were diagnosed positive for endometritis whereas 6 buffaloes having no symptoms of endometritis were considered as healthy control. The blood samples were collected from each animal during diagnosis of endometritis and PBMCs were separated from collected blood samples by density gradient centrifugation. Total RNA was extracted from the cultured PBMCs isolates, reverse transcribed to synthesize the cDNA and amplified in real time PCR system. The relative fold of expression was estimated using 2-∆∆Ct method. An up-regulation in all 3 pro-inflammatory cytokines (IL-1ß, IL-8 and TNFa) mRNA, ranging from 1.92 to 3.27 fold was observed in buffaloes with endometritis as compared to healthy. However, no alteration was detected in anti-inflammatory cytokine, IL-4 expression. Thus, it is concluded that certain cytokines expressed differentially in PBMCs in buffaloes with endometritis, that is first ever information in this species. Nevertheless, further research in respect to threshold level of each target cytokine in peripheral circulation involving more number of animals is required to establish these potential marker gene(s) for diagnosis of endometritis and for monitoring of new therapeutic approaches.